Efektivitas Model Pembelajaran Kooperatif Tipe Make A Match terhadap Pemahaman Konsep Penjumlahan Bilangan Cacah Siswa Sekolah Dasar - Mulyadi, erasafira; Nursupiamin, Nursupiamin; Yulia, Yulia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the differences in mathematics learning outcomes on whole number material between students taught using the Make a Match cooperative learning model and those taught using conventional learning. The method used was a quantitative approach with a quasi-experimental design. The sampling technique employed was total sampling, involving 28 third-grade elementary school students, consisting of 14 students in the experimental class and 14 students in the control class. The research instrument was a 15-item conceptual understanding test that met validity criteria (0.41–0.78) and reliability (Cronbach’s Alpha = 0.87). Data were analyzed using normality tests, homogeneity tests, and an independent samples t-test. The results showed a significant difference between the two groups, with t = 9.170 and Sig. < 0.001. The mean post-test score of the experimental class (86.07) was higher than that of the control class (67.50). In conclusion, the Make a Match cooperative learning model is effective in improving students’ mathematics learning outcomes on whole number material. Keywords : Conceptual Understanding; Cooperative Learning Model; Learning Outcomes; Make a Match; Whole Numbers